Factors Affecting Mobile Waste Recycling through RSCM: A Literature Review - Taher Ben Yahya; Noriza Mohd Jamal; Balan Sundarakani; Siti Zaleha Omain (Recycling, 2021)
Mobile phone consumers have been motivated by the rapid growth of technology and encouraged to update their devices regularly to keep up with new innovations, architectures, and capabilities. Consequently, mobile/cell phone waste has risen significantly in the last decade. Due to their small size, it is convenient for users to keep outdated or unused mobile phones at home or the office, rather than recycling them appropriately. A reverse supply chain (RSC) is one possible method of mitigating the questionable e-waste activity present in the ecosystem. RSC has been significant for the mobile phone industry, user states, analysts, and scholars. This paper reviews the available literature in the RSC management (RSCM) domain, along with its processes and strategies. The paper reviews 223 published scholarly papers in the domain of mobile phone waste recycling and investigates 22 papers related to factors influencing consumers’ intention with regard to electronic recycling, focusing on mobile devices, which contribute significantly to electronic waste management practices.